Resilient nursing in ICU: Aadaptive practices beyond IPC protocols for MDRO management. A qualitative study - Eva Cappelli; Marianna Azzolini; Cristina Ferrari; Federica Canzan (PLoS ONE, 2026)
This descriptive qualitative study explores how resilience among intensive care nurses is activated during the management of patients with multidrug-resistant organisms and how it shapes adherence to infection prevention and control practices under conditions of clinical urgency and organisational pressure. Data were collected between March and June 2025 in two Intensive Care Units through non-participant observations and twenty-one semi-structured interviews involving nurses, a head nurse, nurse assistants, and anaesthesiologists. Interviews were audio-recorded and analysed using inductive content analysis. The analysis identified three interrelated themes encompassing eleven categories: (a) individual and team-based dimensions of nurses’ resilience, (b) adaptive strategies employed by nurses in intensive care settings, and (c) dynamic interactions between professional resilience and organisational support. Resilience emerged as a multilevel and context-dependent process sustained by personal resources, teamwork, and enabling organisational conditions. These elements supported nurses in maintaining adherence to infection prevention and control protocols and safeguarding patient safety, even in highly complex and time-critical situations. However, the findings also revealed a “critical zone” of resilience characterised by constant adaptation, sustained operational pressure, and procedures perceived as difficult to implement in practice, which over time contributed to emotional fatigue and an increased risk of burnout. While professional resilience represents a crucial resource in intensive care, it cannot compensate for structural or organisational shortcomings. Sustainable infection control practices and high-quality care therefore require coherent organisational support systems that extend beyond individual and team-level resilience.